Portal hypertension as an uncommon presentation of hepatic epithelioid hemangioendothelioma: a case report - Zambrano-Huailla, Rommel (2021)
Hepatic epithelioid hemangioendothelioma (HEHE) is a vascular tumor with a low incidence rate. We report a case of a 26-year-old man who was referred to our hospital with a misdiagnosis of liver cirrhosis. On physical examination, ascites was noted. Chest and abdominal computer tomography scans showed coalescent lesions involving the peripheral liver with heterogeneous contrast enhancement and portal vein dilation due to portal hypertension. Extrahepatic metastasis was not observed. The biopsy with immunohistochemical stains suggested HE d CD34). This report describes an uncommon case of HEHE with non-cirrhotic portal hypertension.